2003
DOI: 10.1172/jci200318513
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the 4-sphingenine scaffolds of ceramides in keratinocyte-specific Arnt-deficient mice affects skin barrier function

Abstract: Aryl hydrocarbon receptor nuclear translocator (ARNT), a transcription factor of the Per/AHR/ ARNT/Sim family, regulates gene expression in response to environmental stimuli including xenobiotics and hypoxia. To examine its role in the epidermis, the Cre-loxP system was used to disrupt the Arnt gene in a keratinocyte-specific manner. Gene-targeted, newborn mice with almost normal appearance died neonatally of severe dehydration caused by water loss. Histology showed small changes in the architecture of cornifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 45 publications
(18 reference statements)
2
23
0
Order By: Relevance
“…Additionally, synthesis of phyto‐type sphingolipids correlated with the appearance of hDES2 mRNA during keratinocyte differentiation. Finally, a decrease in mDES2 mRNA in cultured keratinocytes from mice lacking ARNT (transcription factor of the Per/AHR/ARNT/Sim family) was accompanied by a decrease in phytoceramide level [22]. Such correlation supports the hypothesis that phyto‐type sphingolipids are synthesized in mammals by DES2, especially in light of an in vivo study in rats which detected radiolabeled phytosphingosine in the intestine and kidneys following an intravenous injection of [ 3 H]dihydrosphingosine [23].…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, synthesis of phyto‐type sphingolipids correlated with the appearance of hDES2 mRNA during keratinocyte differentiation. Finally, a decrease in mDES2 mRNA in cultured keratinocytes from mice lacking ARNT (transcription factor of the Per/AHR/ARNT/Sim family) was accompanied by a decrease in phytoceramide level [22]. Such correlation supports the hypothesis that phyto‐type sphingolipids are synthesized in mammals by DES2, especially in light of an in vivo study in rats which detected radiolabeled phytosphingosine in the intestine and kidneys following an intravenous injection of [ 3 H]dihydrosphingosine [23].…”
Section: Discussionsupporting
confidence: 66%
“…At present, we do not know whether the expression of these molecules is differentially influenced by HIF-1-independent mechanisms found within colitic tissues (e.g., inflammatory cytokines, reactive oxygen species, etc.). To this end, it was recently shown that conditional deletion of the β chain (ARNT) of HIF by a keratinocyte-specific Cre-recombinase results in neonatal death due to skin barrier defects (45). These studies revealed that death was due to dehydration secondary to changes in skin ceramide compositions.…”
Section: Discussionmentioning
confidence: 99%
“…Th2-skewed immune deviation was evident in the skin lesions and spleen in the transgenic mice, with an elevated circulating IgE level [80]. Interestingly, keratinocyte-specific ARNT -deficient mice generated by a K5 - Cre - loxP system exhibit severe skin barrier dysfunction and die because of rapid dehydration [79]. The keratinocyte-specific ARNT disruption results in significant changes in the amount and composition of ceramides, but not cholesterol and fatty acids.…”
Section: Role Of Ahr/arnt In Epidermal Barrier Functionmentioning
confidence: 99%
“…The most prominent changes in the ceramide composition of the ARNT -null epidermis are observed for ceramide 2 and ceramide 5. The 4-sphingenine that these ceramides normally contain is largely replaced by sphinganine due to the impaired transcription of dihydroceramide desaturase isozyme, Des - 2 [79]. Another type of epidermal ARNT -null mice generated by Geng et al using a K14 - Cre - loxP system also exhibits the upregulation of genes of the epidermal differentiation complex (S100A8, S100A9, S100A10, SPRR1, and SPRR 2) and the alteration of ceramides.…”
Section: Role Of Ahr/arnt In Epidermal Barrier Functionmentioning
confidence: 99%